Comparison of two polymethine dyes used as exciton traps for amphi-PIC J-aggregates - Grynyov, R.S.; Sorokin, A.V.; Guralchuk, G.Ya.; Yefimova, S.L.; Borovoy, I.A.; Malyukin, Yu.V. (Functional Materials, 2008)
Two polymethine dyes of different types (cyanine and squaraine) which possess hydrophobic properties have been used as exciton traps (energy acceptor) for amphi-PIC J-aggregates. Both dyes are found to interact with J -aggregates and reveal strong sensitized luminescence. The comparison of the two dyes has been done to find the most effective trap for incorporation into amphi-PIC J-aggregates. A number of advantages of the squaraine dye over cyanine one have been revealed. This dye is proposed as an effective exciton trap to study the exciton transport in J-aggregates.